Peace education: why and how? - Pamela Baxter (Forced Migration Review, 2005)
Pamela Baxter discusses why peace education programmes are so important and Vick Ikobwa presents the methodology and lessons learned from the UNHCR/INEE Peace Education Programme in East Africa and the Horn.